Amyloid‐β processing in aged s100b transgenic mice is sex dependent - Wartchow, Krista Minéia; Rodrigues, Leticia; Swierzy, Izabela; Buchfelder, Michael; de Souza, Diogo Onofre; Gonçalves, Carlos Alberto; Kleindienst, Andrea (International Journal of Molecular Sciences, 2021)
(1) Background: Calcium‐binding protein S100B is involved in neuroregeneration but has also been associated with neurodegeneration. These contrasting effects may result from concentration or duration of exposure. We investigated the effect of long‐term increased S100B levels on am-yloid‐β processing in one‐year‐old transgenic (tg) mice with 12 copies of the murine S100B gene with specific consideration of sex and specific brain regions. (2) Methods: S100B and amyloid‐β 42 (Aβ42) were quantified in serum, cerebrospinal fluid (CSF), adipose tissue, and different brain regions by ELISA in wild‐type (wt) and S100Btg mice (each n = 7 per group). Thioflavin T (ThT) and Aβ immunostaining were performed for visualization of Aβ deposition. (3) Results: S100B in serum, CSF, and brain was significantly increased in S100Btg mice of both sexes. Aβ42 was significantly increased in the hippocampus of male S100Btg mice (p = 0.0075), and the frontal cortex of female S100Btg mice (p = 0.0262). ThT and Aβ immunostaining demonstrated Aβ deposition in different brain regions in S100Btg mice of both sexes and female wt. (4) Conclusion: Our data validate this experimental model for studying the role of S100B in neurodegeneration and indicate that Aβ processing is sex‐dependent and brain region‐specific, which deserves further investigation of signaling pathways and behavioral responses.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Alzheimer’s disease; Amyloid‐β processing; Neurodegeneration; S100B; Transgenic mice